Hydroalcoholic Extract of Achillea Wilhelmsii Decreases the Expressions of Hippo Signaling Pathway-Associated Oncogenes in the A549 Lung Cancer Cell Line - Nabatchian, Fariba; Davoudi, Maryam; Ashtiani, Mojtaba; Davoudi, Negin; Afrisham, Reza (Current Chemical Biology, 2023)
Background: Achillea wilhelmsii used in traditional Iranian medicine to treat a variety of disorders, has been proven to contribute to some signaling pathways in cancers. Evidence suggests that the Hippo pathway, which regulates organ size, is altered in a few conditions like lung cancer. In this regard, this study aimed to evaluate the effect of the hydroalcoholic extract of this plant on the viability and mRNA expression of some Hippo signaling pathway-associated oncogenes and suppressors in A549 lung cancer cell lines. Methods: Hydroalcoholic extract was prepared using a Soxhlet extractor and its antiproliferative activity was studied by MTT assay. Then, the mRNA expressions of
Keywords: pathway